The PENTINGNYA PENDIDIKAN KEWARGANEGARAAN DALAM MENGATASI KRISIS MORAL DI ERA MILENIAL: JURNAL KEWARGANEGARAAN - Surani, Sofia Dewi Nugraheni; Najicha, Fatma Ulfatun (Prodi PPKn Universitas Slamet Riyadi, 2023)
The moral crisis that is currently hitting the millennium era has raised deep concerns about the moral values ​​of today's society. The ethical crisis in the millennial era is becoming an increasingly deep and complex problem. Various factors, such as the influence of globalization, technological progress, and social change, have shaped the context of individual behavior and weakened basic moral values. In this context, this review examines the importance of citizenship education as the main solution for forming individual character and social ethics in the millennium era. This study discusses the concept of citizenship education, the role of educational institutions and the challenges faced in realizing civic values ​​in education. The research results highlight the importance of citizenship education in overcoming the current moral crisis and emphasize the need for cooperation between government, educational institutions and society to achieve this goal. Key: Citizenship Education, Morals, Millennial Generation